Improving Corrosion Resistance of Magnesium Alloy in Cl(−) Containing Simulated Concrete Pore Solution by Ultrasound-Assisted Chemical Deposition - Wang, Ye (Scanning, 2021)
Coatings are playing an important role in corrosion mitigation of magnesium alloys, and in this study, a facile and eco-friendly chemical deposition process is proposed to improve the corrosion resistance of magnesium-neodymium alloys. The mixture of 1.5 mol/L KH(2)PO(4) solution and 1.2 mol/L CaCl(2) solution is used for reaction solution, and ultrasound is introduced into the process for assisting the chemical deposition. After 40 minutes of the surface treatment, the surface and cross-sectional morphologies are observed by scanning electron microscope (SEM), which reveals that a layer of dense coating is formed on Mg alloy. Energy-dispersive X-ray spectroscopy (EDS) and X-ray Diffraction (XRD) are further combined to analyze the coating, and it is thereby confirmed that this coating mainly consists of CaHPO(4)·2H(2)O. Electrochemical tests and soaking experiments are conducted to evaluate the corrosion resistance of the treated samples in simulated concrete pore solutions. Both the untreated and treated samples have a good corrosion resistance in the Cl(−) free simulated concrete pore solution, but their corrosion behavior is influenced by the introduction of Cl(−) in this study. Fortunately, the coating can protect the substrate effectively in the Cl(−) containing simulated concrete pore solution. In summary, it provides a possible way for magnesium alloys to improve their corrosion resistance when they are used in building engineering.